SOCIAL FUNCTION OF THE TEXT AS A MOTIVATION FOR WRITTEN PRODUCTION - Kohle, Erika Christina [UNESP]; Miller, Stela [UNESP]; Silva Clarindo, Cleber Barbosa da [UNESP] (Univ Estadual Campinas, Fac Educacao, 2020)
This article intends to demonstrate that the teaching of the production of enunciates by means of acts of writing with social function makes possible the appearance of the necessity of this production that brings value to the subjects and motivates them to accomplish such acts. This theme was the object of research carried out with the objective of understanding the processes of appropriation and objectification of discursive genres by children of Elementary Education - Early Years of a recovery and reinforcement project, based on a dialogic approach to teaching mother language, by means of three strategies: (1) promote the teaching of language through the genres of discourse, (2) create motivating conditions for students to appropriate writing, (3) work textual production with a social function. The article brings to the discussion proposals of work developed with the subjects of the research, using theoretical reference that considers the studies of Bakhtin, Volochinov and some authors of the Cultural-Historical Theory, admitting that the dialogue between these studies provides a dynamic vision of language and offers elements that support work with discursive genres in a situation of social use. The data show that, from the production of statements inserted in an extra verbal situation, schoolchildren are more motivated to engage in writing acts that conduct them to the development of language skills that allow the students to perform them whenever necessary both in their school life and out-of-school life.
Keywords: Acts of writing; Discourse genres; Social function of language; Elementary Education - Early Years